Does Sharia Banking Performance Have Varietion between the Region? - Mugiarti, Rini Listia; Khoiruddin, Moh. (Management Analysis Journal, 2018)
The purpose of this research is to know the geographical influence on the performance of Islamic banking which are in different regions. The population in this research is the whole Islamic banking that operations in four regions (Asia, America, Europe, and Africa). Sample based on purposive sampling method there are 16 Islamic banking which comprises 13 banks came from the Asian continent, 1 bank of Americas, 1 banks from continental Europe, and 1 bank comes from the African continent. Methods of analysis used in this study are the analysis of multiple linear regression analysis tools with Eviews 9. The results of the research show that the geographical location of positive and significant effect on the performance of Sharia banking. Variable non-performing financing (NPF) a negative and significant effect on the performance of Sharia banking. Financing to Deposit Ratio (FDR) positive significant effect on the performance of Islamic banking while the Debt to Equity Ratio (DER) does not affect the performance of Islamic banking.